PENGEMBANGAN BAHAN AJAR E-BOOK EKOSISTEM SAWAH BERCIRIKAN ETNOSAINS BERBASIS MOBILE LEARNING KELAS V DI SD/MI - Puji Lestari; Sudi Dul Aji; Farida Nur Kumala (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rice field ecosystem is a crucial topic in elementary IPAS (Integrated Science and Social Studies) education, yet its presentation seldom relates to the local wisdom found in students’ surroundings. Therefore, the development of an ethnoscience-characterized rice field ecosystem e-book, delivered via mobile learning, is expected to enhance fifth graders’ contextual understanding of ecosystem concepts at UPT SD Negeri Resapombo 01. This development study aimed to evaluate the feasibility, practicality, and effectiveness of the e-book, which integrates ethnoscientific values and is accessible on mobile devices. This development research uses the ADDIE model with 5 stages, namely: (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. This research passed due diligence from media experts, material experts and language experts. The subject of this research involved teachers and fourth grade students, through two stages of limited field trials involving 10 students and a large field trial involving 20 students. Data was analyzed based on validation sheet instruments, questionnaires, and tests to assess the improvement in students’ understanding of the subject matter. The feasibility results showed that the media expert gave a score of 95.83%, the language expert 97.5%, and the material expert 90%, with an average feasibility score of 94.44%, categorized as